Association of serum growth differentiation factor-15 with eGFR and hemoglobin in healthy older females. (December 2020) - Yazawa, Hiroko; Fukuda, Taira; Kaneda, Hiroyuki; Waku, Ryutaro; Sakuma, Masashi; Matsumoto, Akihiro; Toyoda, Shigeru; Abe, Shichiro; Nakamura, Fumitaka; Inoue, Teruo; Nakajima, Toshiaki
Abstract: Purpose: Anemia and sarcopenia associated with renal dysfunction caused by cytokine imbalance can contribute to decreased quality of life for older individuals. Growth differentiation factor-15 (GDF-15) is associated with renal dysfunction, although whether it is related to anemia or sarcopenia is unclear. In this study we examined the association of GDF-15 with renal function, hemoglobin and sarcopenia in healthy community-dwelling older females in Japan. Methods: A total of 66 healthy older community-dwelling females (age: 75.8 ± 6.2 years) were enrolled for this study. Skeletal muscle mass index was determined by bioelectrical impedance analysis. Hand-grip strength and walking speed were also assessed. Serum GDF-15 concentration was determined by enzyme-linked immunosorbent assay and both hemoglobin (Hb) level and estimated glomerular filtration rate (eGFR) were measured. Results: Serum GDF-15 levels positively correlated with age but negatively correlated with eGFR and walking speed. In multiple regression analysis, eGFR and hemoglobin (Hb) were independent variables to predict serum GDF-15 levels, even after adjusting for age and body mass index (eGFR: β = −0.423, p < 0.001; Hb: β = −0.363, p = 0.004). Serum GDF-15 level was an independent variable to predict eGFR and Hb. Conclusions: Both Hb and eGFR are predictors for serum GDF-15 concentration in healthy older females. In these community-dwelling older females, renal dysfunction via GDF-15 may be accompanied by anemia, but not sarcopenia.